A history of gold dredging in Idaho - Spence, Clark C., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2016)
A revolution in placer mining from inception in the 1880s until its demise in the 1960s and its impact on Idaho, the nation's fourth leading producer of dredged gold which provides a lens through which to observe the practice and history of gold dredging around the world.
Dredging on the early Snake River -- The black sands craze -- The Burroughs Brothers -- The Pierce area -- The Florence area -- Elk City and Newsome -- Stanley Basin and Yankee Fork -- Salmon City and Leesburg -- South and middle fork of the Boise River -- The Yukon dredge -- The Warren area -- Boise Basin -- Dredging rare metals -- Other dredge grounds -- The struggle for dredge control -- The aftermath: the clean-up.
Keywords: Gold mines and mining -- Idaho -- History; Placer mining -- Idaho -- History